Juridification patterns for social regulation and the WTO: A theoretical framework - Christian Joerges (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
Free Trade has always been highly contested, but both the arguments about it and the treaties that regulate it have changed dramatically since the Second World War. Under the 1947 General Agreement on Tariffs and Trade (GATT) regime, objections to free trade were essentially economic, and tariffs were a nation state's primary means of protecting its interests. However, by the early 1970s, tariffs had been substantially reduced, and the imposition and removal of non-tariff barriers that reflected a wide range of domestic concerns about the protection of health, safety, and the environment have since come to dominate trade agreements and their implementation. The expanding scope of these international treaties, and their effect on domestic regulatory objectives, has created new challenges for the nationstate, and for the international trade system as a whole. Domestic regulatory objectives that are generally embedded in a nation state's legal system or even in its constitution, are now negotiable and are susceptible to adjudication at the international level where they may, or may not, be used to camouflage unrelated economic interests. The international trade system adapted to this situation in 1994 by transforming the GATT into the World Trade Organization (WTO), which has more effective means for dispute resolution and includes a number of special agreements - such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS) and the Agreement on Technical Barriers to Trade (TBT) - with rules for balancing the economic concerns of free trade with the social concerns of regulatory objectives. These developments have generated legal queries about the general legitimacy of transnational governance arrangements and their "constitutionalization", i.e. the quest for transnational governance that is mediated by law and not only accepted de facto but considered deserving of acceptance.
Keywords: 330; Nichttarifäre Handelshemmnisse; Internationale Schiedsgerichtsbarkeit; Normung; WTO-Regeln; Theorie; Welt; Global Governance